1986
DOI: 10.1001/archderm.1986.01660180085021
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Peutz-Jeghers Macules to Psoriatic Plaques

Abstract: We report a case of the Peutz-Jeghers syndrome in which the characteristic pigmented macules developed within preexisting psoriatic plaques in sites extremely unusual for the syndrome. To our knowledge, ours is the first report of such a case in the English literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…An alternative theory is that the PJS freckles are actually benign neoplasms of melanocytes (or some precursor), which have a very limited growth potential and do not seem to increase in size throughout life (Tomlinson and Bodmer, 1996); indeed, PJS pigmentation often fades in middle age. This theory is extremely difficult to test, because PJS freckles are hardly ever biopsied, but is consistent with data showing that PJS pigmentation can occur in proliferative lesions such as psoriatic plaques (Banse-Kupin et al, 1986).…”
supporting
confidence: 67%
“…An alternative theory is that the PJS freckles are actually benign neoplasms of melanocytes (or some precursor), which have a very limited growth potential and do not seem to increase in size throughout life (Tomlinson and Bodmer, 1996); indeed, PJS pigmentation often fades in middle age. This theory is extremely difficult to test, because PJS freckles are hardly ever biopsied, but is consistent with data showing that PJS pigmentation can occur in proliferative lesions such as psoriatic plaques (Banse-Kupin et al, 1986).…”
supporting
confidence: 67%
“…In conclusion, pigmentation should not form the basis of a PJS diagnosis, as similar pigmentation is not rare in the unaffected population [25]. Psoriasis and PJS have been described in the same patient [39]. In addition to the usual loci, the melanin spots were localized also in psoriatic plaques in sites not usually seen in PJS patients: scalp, elbow, buttocks and legs.…”
Section: Review Articlementioning
confidence: 99%
“…Interestingly, macular pigmentation has also been described on psoriatic plaques in patients with PJS . It has been suggested that patients with PJS develop polyps in areas of frequent trauma, such as the bowel and nasopharynx.…”
Section: Reportmentioning
confidence: 99%
“…Interestingly, macular pigmentation has also been described on psoriatic plaques in patients with PJS. 9,10 It has been suggested that patients with PJS develop polyps in areas of frequent trauma, such as the bowel and nasopharynx. Banse-Kupin et al therefore hypothesized that this predisposition could also exist in the skin, with the development of pigmented macules rather than polyps in response to injury.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation